2002
DOI: 10.1038/sj.ijir.3900797
|View full text |Cite
|
Sign up to set email alerts
|

New directions for erectile dysfunction therapies

Abstract: Research in the field of erectile function and dysfunction has continued to expand rapidly. Based on the information available, some directions for future erectile dysfunction therapies can be identified. The first direction is improvement of current therapeutic principles. A second generation of orally active phosphodiesterase (PDE) inhibitors is being introduced, and further developments within this field can be expected. The recent introduction of apomorphine has opened the way for new dopamine receptor ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 74 publications
0
13
0
1
Order By: Relevance
“…The development of the new PDE-5 inhibitors prompts the question of whether and how these three substances differ in terms of their efficacy and adverse effects for a specific category of ED, including SCI patients, allowing the best choice from these oral drugs. 19 Our results showed that the advantage of tadalafil over sildenafil in terms of duration of action was not influenced by level or degree of lesions in SCI men. In our study, two out of five patients (40%) not responding to sildenafil, all with LMN from lumbar incomplete lesions with minimum preservation of reflexive erection, reported to be satisfied after sexual intercourse using tadalafil.…”
Section: Resultsmentioning
confidence: 47%
“…The development of the new PDE-5 inhibitors prompts the question of whether and how these three substances differ in terms of their efficacy and adverse effects for a specific category of ED, including SCI patients, allowing the best choice from these oral drugs. 19 Our results showed that the advantage of tadalafil over sildenafil in terms of duration of action was not influenced by level or degree of lesions in SCI men. In our study, two out of five patients (40%) not responding to sildenafil, all with LMN from lumbar incomplete lesions with minimum preservation of reflexive erection, reported to be satisfied after sexual intercourse using tadalafil.…”
Section: Resultsmentioning
confidence: 47%
“…The differences in these results may be explained by the differences in the doses used between the studies. A number of studies have also reported that in rats, dopamineinduced penile erection seems to involve, particularly, the D 2 -like receptor subtypes, and this seems to be the case also in humans (Heaton, 2000;Andersson and Hedlund, 2002). PNU-95666E is a centrally acting agonist that reportedly activates the D 2 receptor in central dopamine neurons, increases striatal acetylcholine concentrations, and decreases cerebellar nucleotides in rats and mice after systemic administration (Durhama et al, 1997;Heier et al, 1997;Sethy et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The central nervous system (CNS) is an attractive target for discovery of novel therapeutic approaches for the treatment of ED, and many potential sites for CNS-acting drugs have been hypothesized (Andersson and Hedlund, 2002). Pharmacological experiments have focused on the role of neurotransmitters and neuropeptides involved in the central control of erection, via spinal and supraspinal pathways (Andersson, 2001).…”
mentioning
confidence: 99%
“…Although the D2 receptor family seems to be responsible for most of the behavioral effects of dopamine, D1 receptors also may play a role in sexual response. 11 Rodent studies have concluded that dopamine is involved in anticipatory rather than in consummatory motivational sexual responses. Quail models have proposed that dopamine activates a-2-noradrenergic receptors in the MPOA.…”
Section: Neurobiology Of Sexual Responsementioning
confidence: 99%